2016
DOI: 10.1161/jaha.116.003770
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcium Score Improves the Prediction of Occult Coronary Artery Stenosis in Ischemic Stroke Patients

Abstract: BackgroundCoronary heart disease is a significant cause of morbidity and mortality in stroke patients. The coronary artery calcium score (CACS) has emerged as a robust and noninvasive predictor of coronary events. We assessed the predictive ability of CACS to identify stroke patients with severe (≥50%) occult coronary artery stenosis in a stroke/transient ischemic attack population, in addition to the PRECORIS score, based on Framingham Risk Score and presence of cervicocephalic artery stenosis, which was deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
(39 reference statements)
4
6
0
2
Order By: Relevance
“…Sleep apnea, a potential risk factor for CAD, could be used for predicting the presence of hidden CAD. However, previous studies have not investigated the relationship between the CAC score and OSA (7, 8, 22). One study with a large sample size examined the relationship between OSA and CAC in otherwise healthy subjects, including individuals with obesity (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep apnea, a potential risk factor for CAD, could be used for predicting the presence of hidden CAD. However, previous studies have not investigated the relationship between the CAC score and OSA (7, 8, 22). One study with a large sample size examined the relationship between OSA and CAC in otherwise healthy subjects, including individuals with obesity (23).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 30–70% patients with stroke are diagnosed with CAOD, which is associated with long-term cardiovascular outcomes even in patients without any definite clinical history of CAOD (5, 6). Computed tomography-based coronary artery calcium (CAC) score, a non-invasive and simple quantitative measure of atherosclerotic burden in the coronary artery, can be used for the prediction of occult coronary artery disease as a surrogate marker for future cardiovascular events (7, 8). Given the association between the risk of CAOD and prevalence of sleep apnea in an otherwise healthy population (9), the atherosclerotic burden on the coronary artery may be dependent on the severity of sleep apnea in patients with stroke in whom sleep apnea is common.…”
Section: Introductionmentioning
confidence: 99%
“…en Slovaquie en 2012 (71,8%) [ 15 , 16 ]. Par contre, des prévalences plus faibles entre 15 et 40% ont été notées en Tanzanie (Afrique), en Suisse, au Japon et en France [ 2 , 17 - 21 ]. Dans l´étude tanzanienne qui a utilisé l´électrocardiographie comme moyen de dépistage, la faible prévalence retrouvée (23,7%) pourrait s´expliquer par le fait que les séquelles d´infarctus du myocarde étaient le seul critère utilisé pour détecter la coronaropathie [ 2 ].…”
Section: Discussionunclassified
“…12 , 13 Coronary calcification has been examined in many studies as a noninvasive surrogate by which atherosclerosis can be diagnosed and its severity can be assessed. 2 7 In addition, other studies have reported that CCS is helpful for the early detection of asymptomatic atherosclerosis. 11 , 14 Many studies have reported that the CCS measured on CT is a significantly predictive factor for the occurrence of asymptomatic and symptomatic CAD.…”
Section: Discussionmentioning
confidence: 99%
“… 1 6 According to a recent meta-analysis, low-dose coronary computerized tomography (CT) showed that CCS values of 0, 1–99, 100–400, 400–999, and ≥1,000, had 1.0, 1.9, 4.3, 7.2, and 10.8 as relative risk ratio of cardiovascular disease, respectively. 1 , 2 The quantification of CCS has been reported to be a more reliable prognostic factor for cardiovascular disease. 7 , 8 Highly calcified lesion was closely related with poor clinical outcomes due to stent underexpansion and edge dissection.…”
Section: Introductionmentioning
confidence: 99%